Pengembangan Bahan Pembelajaran Pendidikan Moral dengan Metode Diskusi Dilema Moral pada Siswa SMU/SMK - Sihkabuden Sihkabuden (Universitas Negeri Malang, 2016)
The purposes of this study were to develop instructional materials on moral education including the teachers guide, and to develop tests fa-cilitating the implementation of moral dilemma discussion method to SMU/ SMK students; and to investigate the effectiveness of the method through experimental research design. The research results showed that the method had an effect on the process of moral instruction, especially in moral reasoning related to the moral judgement. It is suggested that moral education at SMU/SMK be conducted through moral dilemma discussion method.